1987
DOI: 10.1097/00000658-198703000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Imipenem (N-F-Thienamycin) Versus Netilmicin Plus Clindamycin

Abstract: In a randomized study the clinical and bacteriologic effectiveness of imipenem was compared with the classical combination of netilmicin with clindamycin in patients who had surgery for an intraperitoneal infection, localized or generalized, with positive bacteriologic findings of the specimen taken at surgery. Excluded were all patients who received other antibiotics before surgery, or who died within 3 days after antibiotic therapy was started. Imipenem was given at a dose of 500 mg t.i.d., clindamycin 600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…When carbapenem first became available for treating microbial infections in the 1980s, clindamycin had long been the golden standard for the treatment of anaerobic infections [ 21 ]. Several RCTs, each comparing carbapenem and a conventional combination therapy with clindamycin and aminoglycoside, consistently reported that carbapenem was an effective antimicrobial drug for monotherapy of IAIs with efficacy similar to or better than the combination of clindamycin and aminoglycoside [ 22 25 ]. A meta-analysis of 28 clinical trials also concluded that broad-spectrum β-lactams were more effective than the clindamycin combination therapy in treating IAIs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…When carbapenem first became available for treating microbial infections in the 1980s, clindamycin had long been the golden standard for the treatment of anaerobic infections [ 21 ]. Several RCTs, each comparing carbapenem and a conventional combination therapy with clindamycin and aminoglycoside, consistently reported that carbapenem was an effective antimicrobial drug for monotherapy of IAIs with efficacy similar to or better than the combination of clindamycin and aminoglycoside [ 22 25 ]. A meta-analysis of 28 clinical trials also concluded that broad-spectrum β-lactams were more effective than the clindamycin combination therapy in treating IAIs [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients in the imipenem-cilastatin group received imipenem and cilastatin at dosages of 500 mg of each drug every 8 h as a 30-min intravenous infusion. The imipenemcilastatin doses of 500 mg each every 8 h is the usually recommended dose in Scandinavia for the treatment of moderate infections and has previously been demonstrated to be efficacious in prospective comparative trials (6,12,16); this differs from the usual dose of 500 mg every 6 h used in North America (8,13,14). The recommended dose range for imipenem-cilastatin is 0.75 to 4 g of each drug per day.…”
mentioning
confidence: 99%
“…The efficacy results in the imipenem/cilastatin group are lower than those that have been previously reported [13][14][15][16][17]. The reason for the difference between the two treatments was not apparent in analyzing the microbiology since emergence of imipenem resistance did not occur.…”
Section: Piperacillin/tazobactam Versus Imipenem/cilastatinmentioning
confidence: 55%